Improving the quality of teachers through assessing the teacher’s performance - Madyan Madyan; Mahdayeni Mahdayeni; Maryam Maryam; Khoirul Anwar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
School is a social institution that plays an important role in developing a child's personality. The smooth implementation of education in schools is heavily reliant on the operation of school administration. Management activities, in addition to the principal's leadership in achieving quality schools, are the principal's primary responsibility. A number of dominant factors influence performance appraisal ineffectiveness, including a lack of management commitment to conducting performance appraisal in a systematic manner, performance appraisal methods that are not yet performance-based poor follow-up. Improving teacher quality was discovered to be one of the teacher’s performance evaluation feedbacks that was not running effectively. This is influenced by a number of factors, including uneven awareness of improving teaching discipline, performance appraisal results that are not optimal as a reference in improving teacher quality, reliance on outside institutional assessment programs, a lack of follow-up on the results of upgrading or training attended, and a lack of empowerment to the fullest improvement or development forum in schools. School principals have made efforts to improve teacher’s performance, including routine school meetings, collaboration with supervisors, random teacher’s performance assessments, collaboration with independent teams (school committees), improving reward systems (awards), and motivational training for teachers.